Access to Functionalized 2-Phenyl-4-(Indol-3-yl)-4H-Chromenes via Coupling of 2-Hydroxychalcones and Indole in PEG-400/H2O under Catalyst-free Conditions - Roy, S. (Journal of Scientific Research, 2024)
4H-Chromenes, particularly those appended with functionalized benzene rings at C-4¢ and annulated with heterocycles exhibit a wide array of bioactivities. An innovative molecular scaffold featuring a 4H-chromene motif with a 3-indolyl substituent—an esteemed structural framework—anchored at C-4 was envisaged to expand the bioactivity spectrum of the resultant scaffold. This synthesis employs a straightforward domino approach towards the one-pot synthesis of 2-phenyl-4-(indol-3-yl)-4H-chromenes, utilizing 2-hydroxy chalcones and indoles as readily available starting materials in a PEG-400/H2O (1:1) mixture under catalyst-free conditions. The protocol's green attributes include its atom- and step-economical nature, general applicability, procedural simplicity, hassle-free product isolation, and the use of a nontoxic, environmentally friendly reaction medium.